Pengaruh Pelatihan dan Disiplin Kerja terhadap Kinerja Karyawan: Studi Kasus pada Karyawan di KPO PT.BPR Cipatujah Jabar - Delia Mutia Sobirin; Barin Barlian; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This research aims to find out the effect of simultaneous training and work discipline on employee performance at KPO PT. BPR Cipatujah West Java. Partial effect of training on employee performance at KPO PT. BPR Cipatujah West Java and the partial influence of work discipline on employee performance at KPO PT. BPR Cipatujah West Java. The method used in this study is descriptive with a quantitative approach. With a research sample of 45 people as respondents to KPO PT. BPR Cipatujah West Java based on 45 population data known. The data used is using primary data. The analysis tool used in this study is multiple linear regression using the SPSS support application version. Based on data that have met the validity test, reliability tests and classical assumption tests are processed so as to produce regression equations as follows: Y = 11.067 + 0.293 X1 + 0.433X2. The test results showed that partially the variables used in the study, namely training, had a significant effect on the performance of KPO PT employees. BPR Cipatujah West Java as well as work discipline variables partially affect employee performance. Simultaneously training and work disciplines have a significant effect on employee performance with a f-142,396 value and a signification rate of 0.000. From the calculation of the coefficient of determination obtained the value of R Square of 0.871 or 87.1%. Showed the large influence of training and work discipline on employee performance and the remaining 12.9% is the influence of other variables beyond the variables used in this study.